A genetic algorithm for a flow shop scheduling problem with breakdown interval, transportation time and weights of jobs. (2nd August 2019) - Kumar, Harendra; Kumar, Pankaj; Sharma, Manisha
A flow shop problem exists when all the jobs have the same processing order through the machines. In flow shop problem, the technological demand that the jobs pass between the machines in the same order. The objective of this paper is to find an optimal ordering of 'n' jobs for three machines involving processing times, transportation times, break down interval and weights of the jobs by using genetic algorithm (GA) approach. The proposed algorithm is compared with already published problems in literature. The numerical results show that the present algorithm is a good one within the best well known heuristic algorithms in the field.